Polyphenol-Rich Extract from Propolis Reduces the Expression and Activity of Streptococcus mutans Glucosyltransferases at Subinhibitory Concentrations - Veloz, Jorge Jesús (Biomed Res Int, 2016)
Tooth decay is an infectious disease, whose main causative agent identified is Streptococcus mutans (S. mutans). Diverse treatments have been used to eradicate this microorganism, including propolis. To date, it has been shown that polyphenols from Chilean propolis inhibit S. mutans growth and biofilm formation. However, the molecular mechanisms underlying this process are unclear. In the present study, we assessed the effect of Chilean propolis on the expression and activity of the glycosyltransferases enzymes and their related genes. Polyphenol-rich extract from propolis inhibited gene expression of glycosyltransferases (GtfB, GtfC, and GtfD) and their related regulatory genes, for example, VicK, VicR, and CcpA. Moreover, the treatment inhibited glucosyltransferases activity measured by the formation of sucrose-derived glucans. Additionally, an inhibitory effect was observed in the expression of SpaP involved in sucrose-independent virulence of S. mutans. In summary, our results suggest that Chilean propolis has a dose-dependent effect on the inhibition of genes involved in S. mutans virulence and adherence through the inhibition of glucosyltransferases, showing an anticariogenic potential of polyphenols from propolis beyond S. mutans growth inhibition.